Efektivitas Penggunaan Media Flashcard terhadap Penguasaan Mufrodat Bahasa Arab Siswa Studi Meta Analisis - Muh Hairil; Fatkhul Ulum; Irfan Irfan (Universitas Palangka Raya, 2026)
This study aims to analyze the effectiveness of using flashcard media on students’ mastery of Arabic vocabulary through a meta-analysis experimental approach. The meta-analysis design employed in this study involves the analysis of 20 primary studies published between 2017 and 2025 that met the predetermined inclusion criteria, with a total sample size of 485 in the control group (Nc) and 494 in the experimental group (Ne). The results of the calculation using Comprehensive Meta Analysis (CMA) with a random-effects approach yielded a combined effect size of (g = 1.104; p < 0.000), indicating that flashcard media has a large effect on students’ Arabic vocabulary mastery. This large effect size demonstrates that, overall, flashcard media has a significant impact on improving vocabulary acquisition, thereby accelerating students’ learning processes. Moderator analysis based on educational level, class size, and year of study showed no significant differences (p = 0.786; 0.079; 0.750). These findings strengthen the argument that flashcard media is not only engaging but also effective across various learning contexts. This meta-analysis provides more accurate and reliable conclusions compared to single studies, which are often limited by small sample sizes or narrow contexts. Furthermore, this study offers deeper and more objective insights into the effectiveness of flashcard media in Arabic language learning and can serve as a consideration for educators in addressing challenges in students’ vocabulary mastery.